Offline improvement during motor sequence learning is not restricted to developing motor chunks - Wright, D. L.; Rhee, J.-H.; Vaculin, A. (Journal of Motor Behavior, 2010)
Robust offline performance gains, beyond those that would be anticipated by being exposed to additional physical practice, have been reported during procedural learning and have been attributed to enhancement consolidation, a process by which memory is transformed in such a way that it is not only more resistant to forgetting but may also involve a reorganization of information that supports superior task execution. The authors assessed the impact of increasing within-session practice extent on the emergence of offline performance gains. Practice-dependent improvements occurred across 12 and 24 30-s practice trials of a 5-element motor sequencing task. Offline improvements were observed following both 12 and 24 trials. The improvement following 12 trials was associated with the formation of motor chunks important for establishing movement sequence structure. In contrast, the offline improvement after 24 trials was not related to further changes in movement structure beyond those that had emerged during practice. These data suggest that additional memory operations, beyond those needed to amalgamate subsequences of the SRT task, are susceptible to enhancement consolidation.